Comparison between reverse and traditional screening algorithms for syphilis diagnosis in Hospital Universiti Sains Malaysia - Sidek, Nurul Azira (2021)
Introduction: The global incidence of syphilis increased drastically throughout the world, including Malaysia. Screening algorithm with high sensitivity and specificity should be available to detect syphilis accurately. This study aimed to assess the performance of reverse screening algorithm for syphilis diagnosis in our population. We compare the diagnostic accuracy between two available screening methods: electrochemiluminescence immunoassay (ECLIA) and rapid plasma reagin (RPR), each represents reverse and traditional screening algorithms, respectively. Materials and methods: A total of 206 serum samples were included in this study. These samples were tested with ECLIA, RPR, and Treponema pallidum particle agglutination (TPPA) assay. TPPA was considered as the gold standard test. Reverse and traditional screening algorithms were applied to all specimens. Sensitivity, specificity and predictive values of the screening tests were calculated. ROC curve analysis was used to determine optimal cut-off RPR titer related to TPPA reactivity. Results: Out of 206 serum samples, 32 (15.53%) were diagnosed with syphilis using the reverse algorithm, but only 23 (11.17%) were diagnosed with syphilis using the traditional algorithm. Majority of syphilis cases were male and among  50 years age group. Following the reverse algorithm, 27 (13.11%) cases showed discordant ECLIA and RPR results. Further testing with TPPA reveals that 5 (2.42%) cases are false positive ECLIA. The sensitivity, specificity, PPV and NPV of ECLIA and RPR for syphilis detection were 100%, 97.13%, 86.49%, 100%, and 71.88%, 92.53%, 63.89%, 94.71% respectively. Conclusion: The reverse algorithm showed better performance with higher syphilis detection. ECLIA revealed excellent diagnostic accuracy as a screening test for syphilis with a low false positivity supporting its use in our population. RPR reactivity (titer ≥1:1) should be able to predict the reactivity of confirmatory treponemal test. However, further evaluation with a larger sample size is required.